Time for the Ancients : Measurement, Theory, Experience - Singer, P. N. (2022)
The book presents the author's latest research on ancient perceptions of time; it centres on medical discussions, especially of the doctor-philosopher Galen, while also contextualizing his work within Graeco-Roman evidence and discussions - archaeological, medical, technological, philosophical, literary - more broadly. The focus is on questions of medical or experiential significance: life cycles, disease cycles, daily regimes for mind and body, clinical assessment, including the vital area of diagnosis through the pulse, technologies of time measurement. But the philosophical background is also examined: questions of the nature and definition of time and its relationship to space and motion. Galen offers original contributions in all these areas, at the same time as shedding important light on both contemporary attitudes and previous discussions. The book thus offers an accessible and vivid overview of key issues in ancient time perception and awareness, while also offering the first in-depth exploration of the insights that the Galenic texts add to this picture. Five thematic chapters - Time Measurement, Year and Life Cycles, Biography, Medical Cycles - consider a wide range of evidence and of recent scholarship, while highlighting the contribution of medical texts.